Vital Parameters Detection of Non Stationary Human Subject Using MIMO Radar - Rudrappa, Manjunath Thindlu; Herschel, Reinhold; Knott, Peter (Proceedings International Radar Symposium, 2020)
In this paper, we propose an algorithm based on complex empirical mode decomposition with principle component analysis(CEMD-PCA) which estimates the vital parameters of stationary and moving person, irrespective of the orientation in an extreme clutter and multipath environment. The results obtained were compared against Pulse oximeter(PULOX PO-300) and fitbit wrist band and the average error of heart beat was found to be less than 1%.